Thromboembolisms in Advanced Pancreatic Cancer: A Retrospective Analysis of 475 Patients. Issue 8 (September 2017) - Ishigaki, Kazunaga; Nakai, Yousuke; Isayama, Hiroyuki; Saito, Kei; Hamada, Tsuyoshi; Takahara, Naminatsu; Mizuno, Suguru; Mohri, Dai; Kogure, Hirofumi; Matsubara, Saburo; Yamamoto, Natsuyo; Tada, Minoru; et al.
Abstract : Objectives: Pancreatic cancer is reported to be highly associated with thromboembolism (TE). The aim of this analysis is to clarify risk factors for TE and its clinical impact in Japanese patients with pancreatic cancer. Methods: Data on consecutive pancreatic cancer patients receiving systemic chemotherapy between August 1999 and July 2015 were retrospectively studied. Both symptomatic and asymptomatic, arterial and venous TEs were included in the analysis. Risk factors for TE development were analyzed using a proportional hazards model with death without TE as a competing risk. The impact of TE on survival was also evaluated using a time-dependent covariate multiple Cox model. Results: A total of 475 patients were included in the analysis, and 57 TEs (12%) were identified: 45 venous TEs and 12 arterial TEs. The median time to TE was 169 days and the median survival from TE was 65 days. Liver metastasis was the only significant risk factor for TE (subdistribution hazards ratio, 2.15; P = 0.01), and TE was significantly associated with poor prognosis (hazards ratio, 3.31; P < 0.01). Conclusions: Thromboembolism was not uncommon in Japanese patients receiving chemotherapy for advanced pancreatic cancer and was associated with poor prognosis. Liver metastasis was the risk factor for TE.